Prevalence and influencing factors of chronic post-traumatic stress disorder in patients with myocardial infarction, transient ischemic attack (TIA) and stroke – an exploratory, descriptive study - Aurora Dollenberg; Sebastian Moeller; Caroline Lücke; Ruihao Wang; Alexandra P. Lam; Alexandra Philipsen; Jürgen M. Gschossmann; Falk Hoffmann; Helge H. O. Müller (BMC Psychiatry, 2021)
Abstract Background Cardio- and cerebrovascular events such as myocardial infarction (MI), stroke and transient ischemic attack (TIA) are leading causes of death and disability and have also been associated with poor mental outcomes. In addition, cardio- and cerebrovascular events may pose the risk of experiencing a sudden traumatic occurrence of symptoms during ictus and thus contribute to high rates of PTSD as well as high rates of subsequent depression and anxiety. Moreover, MI, TIA and stroke survivors with PTSD, depressive and anxiety symptoms may have poorer health-related quality of life (HRQoL) and poorer disease prognosis than patients who do not develop psychiatric symptoms after ictus. However, data on the prevalence of PTSD, anxiety and depression, as well as the HRQoL, coping strategies and potential risk factors for development of PTSD in these patients, are rare. Methods In an exploratory, descriptive study we interviewed 112 patients (54 MI, 18 TIA, 40 stroke; mean age: 69.5 years, 55.4% males) from three general physician practices and used psychometric self-assessment tools to determine the occurrence of PTSD and psychosomatic comorbidity, anxiety and depression and to assess HRQoL and coping strategies. We evaluated disease severity and compared the patient groups to each other. Moreover, we assessed psychological outcome differences between patients with or without PTSD after ictus. Results The prevalence of PTSD after MI, TIA and stroke was 23.2%. The patients who developed PTSD had higher rates of depression, anxiety and maladaptive coping as well as reduced HRQoL. Adaptive coping was positively related to better mental HRQoL and negatively related to anxiety and depression. Disease severity of MI, TIA and stroke was not related to PTSD, depression, anxiety or physical HRQoL. Conclusions Experiencing MI, TIA or stroke means confronting a life-threatening event for those affected and, therefore, these can be regarded as traumatic events. Cerebral and cardiovascular events increase the risk of developing chronic PTSD with subsequent increased depression and anxiety and reduced HRQoL. These findings emphasize the need for early screening and diagnosis of PTSD in somatically ill patients, which should be followed by specialized treatment, as PTSD hampers overall (somatic) disease prognosis. Trial registration German Clinical Trials Register, DRKS00021730, https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00021730 , registered 05/19/2020 - Retrospectively registered.